Effects of planting distance on yield of beans (vicia faba l.) under drip irrigation system. - Kakahy, Amer Najat Najmaldeen; Ahmad, Desa; Abdullahi, Abubakar Sadiq (2012)
A study was conducted at the College of Agriculture, Kirkuk University, Iraq to investigate the effects of planting distance on yield of beans (vicia faba I.) under drip irrigation. The yields of three different species of beans (Spanish, Turkish and Local) at three different planting distances of 20, 25 and 30 cm were determined. The result indicates that both the interactions between plant distance and varieties of beans and that of the distance between plants were not significant at 95o/o significant level. However there were significant differences at p < 0.01 for the species of bean based on percentage of growth, plant height, branches/plant, pod length and number of seed/pod, with average values of 94.86, 35.85, 87.50, 10.39 cm, respectively,At p ( 0.05, number of nodes on the plant stem with value 31.37, shows significant effect. However, the differences on the number of branches/plant and weight of pods were not significant.